2017
DOI: 10.1371/journal.pone.0188168
|View full text |Cite
|
Sign up to set email alerts
|

Copy number variants in Ebstein anomaly

Abstract: BackgroundEbstein anomaly (EA) is a rare congenital defect characterized by apical displacement of the septal tricuspid leaflets and atrialization of the right ventricle. The etiology of EA is unclear; however, recurrence in families and the association of EA with genetic syndromes and copy number variants (CNVs) suggest a genetic component.ObjectiveWe performed a population-based study to search for recurrent and novel CNVs in a previously unreported set of EA cases.MethodsWe genotyped 60 EA cases identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
(68 reference statements)
0
4
0
1
Order By: Relevance
“…Among 3463 genes with Episcore > 0.6, 1518 have pLI scores < 0.5. Some of these genes have been implicated in human diseases under a dominant model, such as HEY2 32 , ASF1A 33 , and HAND2 34 (Supplementary Table 1 ). Similarly to the ones with low pLI values in the positive training set, these genes have lower background mutation rate (which is primarily determined by transcript size) than the ones with large pLI values (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among 3463 genes with Episcore > 0.6, 1518 have pLI scores < 0.5. Some of these genes have been implicated in human diseases under a dominant model, such as HEY2 32 , ASF1A 33 , and HAND2 34 (Supplementary Table 1 ). Similarly to the ones with low pLI values in the positive training set, these genes have lower background mutation rate (which is primarily determined by transcript size) than the ones with large pLI values (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17] Abnormal CUX1 expression is associated with the Ebstein anomaly, which affects cardiomyocytes and myocardium differentiation. 18 IRX6 was associated with point mutations and small insertions/deletions in a Dutch Brugada syndrome cohort. 19 In the current study, a PPI network analysis showed that ASB1 was defined as a hub gene and played important roles in PPIs in HF.…”
Section: Discussionmentioning
confidence: 97%
“…19 In the current study, a PPI network analysis showed that ASB1 was defined as a hub gene and played important roles in PPIs in HF. ASB1 is a member of the ankyrin repeat and SOCS box-containing (ASB) family of proteins (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The ASB1 gene, located on chromosome 2q37, encodes a protein with 335 amino acids.…”
Section: Discussionmentioning
confidence: 99%
“…Генами-кандидатами являются MYH7 и NKX2-5. У носителей порока нередко выявляется миссенс-мутация FLNA (филамин А, актин-связывающий протеин) на Xq28 [3][4][5][6]. У родственников редко обнаруживаются мутации кардиального фактора транскрипции NKX2-5, делеции 10p13-p14 и 1p34.3-p36.11 [7].…”
Section: распространенность и возможные причинные факторыunclassified